Morphological and physiological responses of lowland purple nutsedge (Cyperus rotundus L.) to flooding - Fuentes, Rolly G.; Baltazar, Aurora M.; Merca, Florinia E.; Ismail, Abdelbagi M.; Johnson, David E. (Oxford University Press, 2010)
Purple nutsedge (Cyperus rotundus L.) is a major weed of upland crops and vegetables. Recently, a flood-tolerant ecotype evolved as a serious weed in lowland rice. This study attempted to establish the putative growth and physiological features that led to this shift in adaptation. Tubers of upland C. rotundus (ULCR) and lowland C. rotundus (LLCR) ecotypes were collected from their native habitats and maintained under the respective growth conditions in a greenhouse. Five experiments were conducted to assess the variation between the two ecotypes in germination, growth and tuber morphology when grown in their native or ‘switched’ conditions. Carbohydrate storage and mobilization, and variation in anaerobic respiration under hypoxia were compared. Tubers of LLCR were larger than those of ULCR, with higher carbohydrate content, and larger tubers developed with increasing floodwater depth. Stems of LLCR had larger diameter and proportionally larger air spaces than those of ULCR: a method of aerating submerged plant parts. The LLCR ecotype can also mobilize and use carbohydrate reserves under hypoxia, and it maintained relatively lower and steadier activity of alcohol dehydrogenase (ADH) as a measure of sustained anaerobic respiration. In contrast, ADH activity in ULCR increased faster upon a shift to hypoxia and then sharply decreased, suggesting depletion of available soluble sugar substrates. The LLCR ecotype also maintained lower lactate dehydrogenase activity under flooded conditions, which could reduce chances of cellular acidosis. These adaptive traits in the LLCR ecotype were expressed constitutively, but some of them, such as tuber growth and aerenchyma development, are enhanced with stress severity. The LLCR ecotype attained numerous adaptive traits that could have evolved as a consequence of natural evolution or repeated management practices, and alternative strategies are necessary because flooding is no longer a feasible management option.